2020
DOI: 10.1186/s13578-020-00440-0
|View full text |Cite
|
Sign up to set email alerts
|

KLF13 suppresses the proliferation and growth of colorectal cancer cells through transcriptionally inhibiting HMGCS1-mediated cholesterol biosynthesis

Abstract: Background: Colorectal cancer (CRC) is the fourth most deadly malignancy throughout the world. Extensive studies have shown that Krüppel-like factors (KLFs) play essential roles in cancer development. However, the function of KLF13 in CRC is unclear. Methods: The Cancer Genome Atlas database was applied to analyze the expression of KLF13 in CRC and normal tissues. Lentivirus system was used to overexpress and to knock down KLF13. RT-qPCR and Western blot assays were performed to detect mRNA and protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…KLF13 knockdown could effectively promote cell proliferation and colony formation. Opposite results were observed in KLF13 overexpressed cells [ 27 ]. In the further research, Yao et al found that KLF13 transcriptionally inhibited HMGCS1 and knockdown of HMGCS1 could suppress the proliferation of colorectal cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…KLF13 knockdown could effectively promote cell proliferation and colony formation. Opposite results were observed in KLF13 overexpressed cells [ 27 ]. In the further research, Yao et al found that KLF13 transcriptionally inhibited HMGCS1 and knockdown of HMGCS1 could suppress the proliferation of colorectal cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 84%
“…Opposite results were observed in KLF13 overexpressed cells [ 27 ]. In the further research, Yao et al found that KLF13 transcriptionally inhibited HMGCS1 and knockdown of HMGCS1 could suppress the proliferation of colorectal cancer [ 27 ]. But in the present study, we found that the expression of HMGCS1 was decreased significantly in KIRC.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…5C ). It has been reported that HMGCS1 is an important factor for cholesterol biosynthesis [ 52 ]. So, we further confirmed the decreased protein level of HMGCS1 in YAP −/− astrocytes by western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, KLF13 is involved in lipid metabolism, and it transcriptionally inhibited HMGCS1-mediated cholesterol biosynthesis in colorectal cancer. 21 In the present study, we performed bioinformatics analysis and identified that ACOT7 was transcriptionally regulated by KLF13.…”
Section: Introductionmentioning
confidence: 92%